Propriedades termodinâmicas, eletrônicas e de transporte de sistemas curvos semicondutores - Batista Júnior, Francisco Florêncio (2014)
We study thermodynamic properties of an electron gas confined in a two-dimensional cylindrical surface under the action of a magnetic field perpendicular to the cylinder axis. We observed that the applied magnetic field has a similar effect to that produced by a non-homogeneous magnetic field on a flat system. We calculate the energy spectrum of the system for different values of curvature and symmetry of the magnetic field to the surface. We show that the physical properties of these systems are strongly connected to the symmetry imposed by the magnetic field by calculating the density of states, specific heat and chemical potential. We investigate how the curvature of a semiconductor film affects its electronic and transport properties. We study how the geometry-induced potential resulting exclusively from periodic ripples in the film modifies its band structure by inducing electronic confinement. For fixed curvature parameters, this confinement can be easily tuned by an external electric field, so that features of the band structure such as the energy gaps and band curvature can be controlled by an external parameter. We also show that, for some values of curvature and electric field, it is possible to obtain massless Dirac bands for a smooth structure. Moreover, we use a wave packet propagation method to demonstrate that the ripples are responsible for a significant inter-sub-band transition, specially for moderate values of the ripple height.